Situation Report: Baltic Area, 9 September 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Preparations for the Constituent Congress of the People's Front / by Dzintra Bungs Toward Education in Minority Languages / by Dzintra Bungs A New Program for Teaching Latvian History / by Dzintra Bungs Daring Poster Art / by Dzintra Bungs A Change of Policy in the Lithuanian Communist Party / by Kestutis Girnius Ecology Rally in Kaunas Attended by 500,000 People / by Saulius Girnius Construction Suspended at Ignalina Atomic Power Plant / by Saulius Girnius